2018
DOI: 10.5430/jnep.v8n6p93
|View full text |Cite
|
Sign up to set email alerts
|

The effect of reference position versus right lateral position on the intra-abdominal pressure in mechanically ventilated patients

Abstract: Background and objective: Intra-abdominal hypertension (IAH) is a frequent plentiful problem in patients admitted to critical care units. It ranges from a surge incidence of morbidity and mortality to a particular need for nursing health care, so recognition of the occurrence of IAH is a very critical issue for critical care nurses and physician. This study aimed to recognize the effects of various body position with the various head of bed elevation on the intra-abdominal pressure (IAP) in patients with mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
1
0
0
Order By: Relevance
“…In this regard, non-randomized, prospective study of Mahran et al, to investigate the effect of lateral position on intra-abdominal pressure compared to supine position in patients undergoing mechanical ventilation. This study showed that when the patient's body position changes from supine to lateral, the mean intraabdominal pressure increases [26], which was consistent with the results of our study.…”
Section: Discussionsupporting
confidence: 93%
“…In this regard, non-randomized, prospective study of Mahran et al, to investigate the effect of lateral position on intra-abdominal pressure compared to supine position in patients undergoing mechanical ventilation. This study showed that when the patient's body position changes from supine to lateral, the mean intraabdominal pressure increases [26], which was consistent with the results of our study.…”
Section: Discussionsupporting
confidence: 93%